Clinical Supervision and Emotional Intelligence Capabilities: E Excellence in Clinical Practice - Cruz, Sandra (2015)
We carried out a study to relate the implementation of a clinical supervision (CS) model with the supervised nurses’ emotional intelligence capabilities. 38 paired questionnaires with the Portuguese version of the Manchester Clinical Supervision Scale© (MCSS©) and the Veiga Branco Emotional Intelligence Capabilities Scale (VBEICS©) were obtained. SPSS© version 18.0 was used to treat data. We verified a significant weak correlation between the ‘self-motivation’ subscale of the VBEICS© and the ‘personal issues’ subscale of the MCSS© (-0,386). Our study pointed out that when the supervised nurses were more self-motivated they discussed less personal issues.